Răspuns :
( x + 2 ) ³ - ( x + 2 ) = ( x +2 ) · [ (x +2 ) ² - 1 ² ] =
↓ formula = diferenta patratelor
=1 = 1 ²
= ( x +2 ) · ( x +2 + 1 ) · ( x + 2 - 1 ) =
= ( x +2 ) · ( x + 3 ) · ( x + 1 )
↓ formula = diferenta patratelor
=1 = 1 ²
= ( x +2 ) · ( x +2 + 1 ) · ( x + 2 - 1 ) =
= ( x +2 ) · ( x + 3 ) · ( x + 1 )
(x+2)³-x-2=(x+1)(x+2)(x+3)
(x+2)³-(x+2)=(x+1)(x+2)(x+3)
(x+2)[(x+2)²-1]=(x+1)(x+2)(x+3)
(x+2)(x²+4x+4-1)=(x+1)(x+2)(x+3)
(x+2)(x²+4x+3)=(x+1)(x+2)(x+3)
(x+2)(x²+3x+x+3)=(x+1)(x+2)(x+3)
(x+2)[x(x+3)+(x+3)]=(x+1)(x+2)(x+3)
(x+2)(x+3)(x+1)=(x+1)(x+2)(x+3)∨x∈R
(x+2)³-(x+2)=(x+1)(x+2)(x+3)
(x+2)[(x+2)²-1]=(x+1)(x+2)(x+3)
(x+2)(x²+4x+4-1)=(x+1)(x+2)(x+3)
(x+2)(x²+4x+3)=(x+1)(x+2)(x+3)
(x+2)(x²+3x+x+3)=(x+1)(x+2)(x+3)
(x+2)[x(x+3)+(x+3)]=(x+1)(x+2)(x+3)
(x+2)(x+3)(x+1)=(x+1)(x+2)(x+3)∨x∈R